Behind the headlines: modality in Malaysian news media on foreign labour recruitment - C Suppiah, Puspalata; Mohd Noor, Maizura; Turiman, Syamimi; Azizan, Mazlin; Aziz, Muhammad Nasiruddin; Shamshul Bahrn, Fatin Fatinah (Universiti Teknologi MARA, Kedah, 2025)
The interest in the influx of foreign workers to Malaysia has consistently captured the attention of society, a sentiment evident in much of the Malaysian media. This article specifically explores the editorials discussing the recruitment of foreign workers in mainstream Malaysian English-language newspapers through the lens of Critical Discourse Analysis, with a focus on examining the use of modality in conveying meaning. Data for this research were deliberately chosen from two prominent English-language newspapers: The Star and New Straits Times. The analysis of the data was conducted manually, considering various functions of modal auxiliary verbs, and drawing insights from Halliday’s model of Systemic Functional Grammar (SFG). Martin's Positive Discourse Analysis (PDA) was also integrated to enhance the understanding of the relationship between linguistic features and social context in the meaning-making process from a positive perspective. The study indicates that editorial writers employ a variety of linguistic strategies, particularly through modality, to convey different attitudes and opinions. These strategies subtly contribute to positively influencing and shaping readers' perspectives towards the issue at hand. This propagation of positive information fosters critical thinking and cultivates a more informed readership. By emphasising the pivotal role of linguistic strategies in news reporting, particularly in challenging potentially negative perceptions held by readers, this study aims to provide a different perspective on matters related to the recruitment of foreign workers. It is anticipated that this research will be of interest not only to the social sciences but also to the fields of arts and humanities.